Contraceptive Practices and Awareness of Emergency Contraceptive Pills among Rural Women of Reproductive Age (Central Medical College Journal, 2023)
Background: Regular contraceptive use and emergency contraception are tools to prevent population explosion. Objective: To assess the contraceptive practices and awareness of emergency contraceptive pills among rural women of reproductive age. Methods: The cross sectional study is conducted over 3months (December 2021 to February 2022) among 345 women of reproductive age (15-49 years) who living with their husbands in selected rural residence at Mostafapur village under Sadar Upazilla in Cumilla district. Women who were pregnant, had a child younger than 2 years, or had any physical & psychological disorder were excluded. Participants are selected by convenience sampling technique, data are collected by face to face interview with a semi-structured questionnaire to assess socio-demographic characteristics, contraceptive practices and awareness of emergency contraceptive pills. Data are analysed by SPSS software. Results: In this study, majority (48.7%) of the participants are in the age group 25-34 years. Most of them are housewives (92.2%) and 33.0%has secondary education. The mean (±SD) monthly family income of the participants is 25463.77 (±15971.158) tk and 58.3% of the participants has 1-2 children. About the current practice of contraceptive method, 52.2% of the participants practice and OCP is the widely used method (58.3%), 44.40% take decision by both husband and wife. About reasons for using contraceptives, majority (38.3%) of them use due to spacing of birth and 27.2% cases do not use due to husband disapproval. Regarding awareness of ECPs, 55.9% of them aware of and Norpill is the widely heard method (20.7%). 27.4% of the participants’ source of information is frommedia: TV/Radio. About correct time of taking ECPs, 33.60%of them have no knowledge. Regarding conditions where ECPs are to be taken, majority 39.7% of them have no knowledge. About benefits of taking ECPs, majority (79.30%) of them know it can prevent pregnancy. Conclusion Contraceptive practices and awareness of ECPs are not satisfactory among rural women. So national wide campaign program should be conducted to improve this field.Central Medical College Journal Vol 6 No 1 January 2022 Page: 22-27